الكفاية المعرفية و علاقتها بأداء الطالب المتربص خلال حصة التربية البدنية و الرياضة من وجهة نظر الأساتذة - حفصي العيد; يحي بن حفاف (My University, 2025)
هدفت هذه الدراسة إلى الكشف عن علاقة الكفاية المعرفية بأداء الطالب المتربص خلال حصة التربية البدنية والرياضة من وجهة نظر الأساتذة، وذلك انطلاقا من أهمية المعارف التربوية والبيداغوجية في توجيه الممارسة الميدانية واعتمدت الدراسة على المنهج الوصفي التحليلي من خلال استبيانات وملاحظات ميدانية قدمها أساتذة مكوّنون بجامعات مختلفة، قصد تحديد مستوى امتلاك الطلبة المتربصين للرصيد المعرفي وأثره في تسيير الحصص وإنجاحها وأظهرت النتائج أن الطلبة الذين يمتلكون قاعدة معرفية متينة يكونون أكثر قدرة على التخطيط الجيد، وضبط الأنشطة، والتكيف مع المواقف الطارئة، مما ينعكس إيجابا على أدائهم الميداني. كما تبين أن ضعف الكفاية المعرفية يؤدي إلى قصور في الأداء ويحد من فاعلية الحصة وخلصت الدراسة إلى ضرورة تعزيز الجانب المعرفي في برامج التكوين الجامعي وربط المعارف النظرية بالممارسة العملية لضمان إعداد أساتذة أكفاء قادرين على قيادة العملية التربوية بفعالية.
This study aimed to explore the relationship between cognitive competence and student trainee performance during physical education and sports classes from the teachers' perspectives. This stems from the importance of educational and pedagogical knowledge in guiding field practice. The study relied on a descriptive-analytical approach, using questionnaires and field observations provided by professors trained at various universities. The aim was to determine the level of knowledge acquired by student trainees and its impact on the management and success of classes. The results showed that students with a solid knowledge base are better able to plan well, control activities, and adapt to emergency situations, which positively impacts their field performance. It also demonstrated that weak cognitive competence leads to deficient performance and limits the effectiveness of the class. The study concluded that it is necessary to strengthen the cognitive aspect of university training programs and link theoretical knowledge with practical practice to ensure the preparation of competent teachers capable of effectively leading the educational process. Keywords: cognitive competence, pedagogical performance, student trainee, physical education, university training, professors' perspectives.